2015
DOI: 10.1016/j.jmau.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Histodifferentiation and ultrastructure of nodular cultures from seeds of Vriesea friburgensis Mez var. paludosa (L.B. Smith) L.B. Smith and leaf explants of Vriesea reitzii Leme & A. Costa (Bromeliaceae)

Abstract: Micropropagation via induction, multiplication and development of nodular cultures (NCs) is an efficient regeneration system for Bromeliaceae, a family of endangered monocot plants with ornamental value. Therefore, the present work aimed to induce NCs from seeds and leaf explants of Vriesea in order to characterize the morphological and histochemical aspects of induction and formation of these cultures. Seeds of Vriesea friburgensis var. paludosa were sterilized and inoculated into liquid culture media supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The regular cell composition on the surface in comparison with regions beyond the PT, the presence of starch granules, and the shoot buds arising on the PT can be mentioned as the most relevant. These features are similar to the histology of protocorm-like bodies or the multiple meristem-like tissues observed in Orchidaceae (Zhao et al 2008 ; Chen et al 2019 ) and nodular cultures in Bromeliaceae (Corredor-Prado et al 2015 ). However, the histological organization of PT in kiwifruit also resembles PT observed in other woody vines— Passiflora edulis (Fernando et al 2007 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The regular cell composition on the surface in comparison with regions beyond the PT, the presence of starch granules, and the shoot buds arising on the PT can be mentioned as the most relevant. These features are similar to the histology of protocorm-like bodies or the multiple meristem-like tissues observed in Orchidaceae (Zhao et al 2008 ; Chen et al 2019 ) and nodular cultures in Bromeliaceae (Corredor-Prado et al 2015 ). However, the histological organization of PT in kiwifruit also resembles PT observed in other woody vines— Passiflora edulis (Fernando et al 2007 ).…”
Section: Discussionsupporting
confidence: 75%
“…The relationship between the appearance of PTs or outgrowths and the emergence of primordia-like structures or shoot buds has been observed during tissue culturing of different species (Nakano and Maeda 1974 ; Jarret et al 1981 ; Fernando et al 2007 ; Daffalla et al 2011 ; Qiao et al 2012 ; Tekdal and Cetiner 2013 ; Manivannan et al 2015 ; Lee and Pijut 2017 ). However, morpho-histological data about organogenic calluses are focused mainly on structures referred to as protocorm-like bodies (Zhao et al 2008 ; Palama et al 2010 ; Chen et al 2019 ) or nodular structure formation (Oka et al 1982 ; Rocha et al 2012 ; Corredor-Prado et al 2015 ). Histological and ultrastructural studies describing the origin and different stages of in vitro morphogenesis have contributed significantly to the understanding and optimization of regeneration systems (Rocha et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, NAA in the culture medium altered the seedling development for NCs induction. Other studies have reported the effect of auxins combined with cytokinins, which also caused NCs induction from Vriesea seeds but at lower percentages (Dal Vesco et al, 2014a;Corredor-Prado et al, 2015). In morphogenetic routes, such as somatic embryogenesis, several steps including dedifferentiation and somatic cells reprogramming, are necessary for the initiation and progression of development programs (Zhang & Ogas, 2009).…”
Section: Resultsmentioning
confidence: 96%
“…NCs are defined as groups or conglomerates of organogenic nodules with high regenerative efficiency Dal Vesco et al, 2011). Strategies for induction of NCs in bromeliads include nodal segments (Dal Vesco, Stefenon, Welter, Guerra, & Scherer, 2011), leaf segments (Alves, Dal Vesco, & Guerra, 2006;Scherer et al, 2013;Dal Vesco, Vieira, Corredor Prado, Guerra, & Elter, 2014b) and seeds (Dal Vesco, Pescador, Corredor Prado, Welter, & Guerra, 2014a;Corredor-Prado et al, 2015). This work has established a system of NCs induction and regeneration of shoots in response to different types and combinations of plant growth regulators (PGRs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation